Hubungan Antara Empati dengan Perilaku Prososial Siswa SMA - Nabilla Khairun Nisa; Rezki Hariko; Lisa Putriani; Azmatul Khairiah Sari (Scidacplus, 2026)
The phenomenon of declining social awareness among adolescents indicates that prosocial behavior has not developed optimally, which is thought to be related to low levels of individual empathy. Empathy, as the ability to understand and feel the emotional conditions of others, plays an important role in encouraging the emergence of prosocial behavior. This study aims to describe the level of empathy, describe the level of prosocial behavior, and examine the relationship between empathy and prosocial behavior in high school students. The respondents of this study were 254 students of SMA Negeri 4 Pariaman in grades X, XI, and XII, selected through a stratified random sampling technique. The study was conducted with a quantitative approach using a correlational method. The instruments used were the Student Empathy Scale and the Student Prosocial Behavior Scale using a Likert scale. Data were analyzed using the Pearson Product-Moment correlation test with the help of SPSS software version 27.0 for Windows. The results showed that the level of empathy was generally in the high category (65.75%), while the level of prosocial behavior was generally in the medium category (63.39%). The correlation analysis of the two variables showed a significant and positive relationship (r = 0.643; p <0.05). The research results show that higher empathy tends to increase prosocial behavior. These findings should serve as a basis for school counselors and educational institutions in designing programs and interventions to enhance and develop empathy and prosocial behavior in students.